A study on gender, tax agent, age, income level, tax return and business sectors towards tax evasion - Wodjin, Christina (2018)
Tax evasion is alarming in Malaysia as more stringent measures are employed by Inland Revenue Board Malaysia (IRBM) to tackle this existing concerns. In general, tax evasion is an illegal act of non-payment or under payment of tax. Although many studies on tax evasion were carried out in the past, there are still limited studies that used proprietary tax audit data to identify the association between taxpayers’ characteristics and tax evasion. Hence, this study will determine the significant difference between gender, tax agent engagement, age, income level, tax return filing experience and business sectors with tax evasion especially among taxpayers with business income in Klang Valley, Malaysia which has been identified to have low compliance rate in year assessment 2015. This study also employs actual data on the imposed penalty as a proxy in measurement for tax evasion. The results show that gender, age, income level, and tax return filing experience have significant difference with tax evasion while tax agent engagement and business sectors have no significant difference with tax evasion. The results of this study are highly relevant to IRBM in developing strategies to curb tax evasion as well as add value to the current works on literature related to taxation.